"Digital" Water Utilities Rely on Data Analytics and Sharing. Issue 10 (5th October 2020) - Stillman, Jeff; Buxton, Jeff; Chastain‐Howley, Andrew; Strayer, James
Abstract : According to Black & Veatch's 2020 Strategic Directions: Water Report (https://bit.ly/2ZIvlNI ), based on a survey of nearly 300 water industry stakeholders, more than three‐quarters of respondents reported they were collecting a lot of data, but just one‐fifth said they were leveraging data effectively for digital transformation. This implies that most utilities have a long way to go to unleash the true value of their data.